2021
DOI: 10.26434/chemrxiv-2021-67nq5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Standard binding free energy and membrane desorption mechanism for a phospholipase C

Abstract: Peripheral membrane proteins (PMPs) bind temporarily to cellular membranes and play important roles in signalling, lipid metabolism and membrane trafficking. Obtaining accurate membrane-PMP affinities using experimental techniques is more challenging than for protein-ligand affinities in aqueous solution. At the theoretical level, calculation of standard protein-membrane binding free energy using molecular dynamics simulations remains a daunting challenge owing to the size of the biological objects at play, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 67 publications
(114 reference statements)
0
4
0
Order By: Relevance
“…Recent work to calculate the absolute membrane binding free energy for Bt PI-PLC used a geometrical route and an atomistic force field to progressively detach the protein from the bilayer [ 26 ]. Along with a value for ΔG 0 bind (which agrees moderately well with the value from fluorescence correlation spectroscopy binding data for Bt PI-PLC binding to PC SUVs), the method provides atomic-level details that describe the membrane-bound protein and how interactions change during the desorption process.…”
Section: Computational Results—identification Of Pc Binding Sites On ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work to calculate the absolute membrane binding free energy for Bt PI-PLC used a geometrical route and an atomistic force field to progressively detach the protein from the bilayer [ 26 ]. Along with a value for ΔG 0 bind (which agrees moderately well with the value from fluorescence correlation spectroscopy binding data for Bt PI-PLC binding to PC SUVs), the method provides atomic-level details that describe the membrane-bound protein and how interactions change during the desorption process.…”
Section: Computational Results—identification Of Pc Binding Sites On ...mentioning
confidence: 99%
“…So far, there are only a few other peripheral membrane proteins where PC-cation–aromatic Tyr/Trp/Phe complexes have been identified and shown to be important for membrane binding. These include a number of phospholipases in addition to Bt PI-PLC: the cytosolic phospholipase A 2 , whose C 2 domain forms a PC-cation–Tyr-π complex that is also stabilized by a Ca +2 interacting with the lipid phosphate group [ 33 ]; phospholipase A 2 Naja naja atra , where ΔΔG data are available for replacing aromatic amino acids by Ala [ 34 ], and the PC specificity was shown to arise from cation-π complexes by simulations [ 26 ]; and a spider phospholipase D that uses Tyr cages around the bound PC cation [ 35 ]. The PC cation-π formation in the PLD appears conserved in many of the other members in the same clade, emphasizing these are distinct complexes that are useful for ensuring PC specificity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the ratio between basic and hydrophobic amino acids varies between PMPs, from strong unspecific electrostatics to proteins with barely any basic cluster [21][22][23]. We have shown that lysine side chains might engage in hydrophobic contacts [23,24] and that the role of aromatic amino acids appears to be more elaborate than a mere hydrophobic anchor. The side chains of tyrosines and tryptophanes are instead able to take advantage of a wider palette of chemical interactions and insertion depths than first thought [25][26][27][28].…”
Section: Introductionmentioning
confidence: 86%
“…For example, the ratio between basic and hydrophobic amino acids varies between PMPs, from strong unspecific electrostatics to proteins with barely any basic cluster [ 20 22 ]. We have shown that lysine side chains might engage in hydrophobic contacts [ 22 , 23 ] and that the role of aromatic amino acids appears to be more elaborate than a mere hydrophobic anchor. The side chains of tyrosines and tryptophanes are instead able to take advantage of a wider palette of chemical interactions and insertion depths than first thought [ 24 27 ].…”
Section: Introductionmentioning
confidence: 99%